Elastase-Induced Intracranial Dolichoectasia Model in Mice. Issue 3 (16th January 2015) - Dai, Daying; Kadirvel, Ram; Rezek, Issa; Ding, Yong-Hong; Lingineni, Ravi; Kallmes, David
Abstract: BACKGROUND: Intracranial dolichoectasia is associated with high morbidity, and its pathophysiology remains poorly understood. OBJECTIVE: To develop a technique for the creation of a murine model of dolichoectasia. METHODS: C57/BL6 mice were injected with 0 milliunit (mu) (control, n = 5), 15 mu (n = 7), 25 mu (n = 10), 35 mu (n = 10), and 55 mu (n = 6) of elastase in the cisterna magna. Fourteen days after injection, the vasculature of the brain was perfused with MicroFil polymerizing compound. Tortuosity index and the percentage increase in arterial diameter were calculated for the basilar artery, posterior communicating arteries, and the A1 segment of the anterior cerebral arteries. Tortuosity index >10 combined with 25% increase in diameter were used to indicate success in achieving dolichoectasia. RESULTS: The mortality rate was 28%, 30%, 80%, and 83% in the 15, 25, 35, and 55 mu groups, respectively. As the 35 and 55 mu groups experienced unacceptable mortality rates, they were excluded from further analysis. The tortuosity index and percent increase arterial diameter of the 15 and 25 mu groups for the left anterior cerebral arteries, right anterior cerebral arteries, left posterior communicating arteries, right posterior communicating arteries, and basilar artery were significantly higher (TI >10 and arterial diameter >25%) than in the control. There was no significant difference in tortuosity index or artery diameter between the 15 and 25 mu groups for any of the 5 artery segments. CONCLUSION: Elastase injection through the cisterna magna can induce intracranial dolichoectasia in mice. Fifteen to 25 mu of elastase is an appropriate dose to use with acceptable mortality.